Teaching English to young learners through stories: Implementing story-based language teaching methodology in pre-service teacher training - Ilona Lekhner; Baran Ielyzaveta; Fábián Márta; Huszti Ilona; Bárány Erzsébet; Lechner Ilona; Фабіян Марта; Лехнер Ілона; Барань Єлизавета; Густі Ілона (PoliPrint Kft, 2011)
Abstract. The value and benefits of teaching a modern language to young learners through stories have been established and acknowledged by researchers (Ellis & Brewster, 1991; King, 2003; Lugossy, 2007; Mattheoudakis, Dvorakova & Láng, 2007). In Transcarpathia in western Ukraine, however, this teaching strategy is not widely spread, despite the proven motivating characteristics of stories and their positive influences on language learning success. Therefore, we find it of utmost importance to introduce English major students (pre-service teachers of English) to the methodology of using stories in the young learner English classroom. English major and Ukrainian major pre-service teachers participated in the research we have carried out. Their journals were collected and analysed qualitatively. The results show that the story-based teaching has positive impacts on young learners’ listening comprehension and vocabulary development. Besides, it raises learner motivation towards learning the English language. Expected advantages and benefits of the research project were that trainee teachers would learn the methodology of teaching modern foreign languages to young learners through stories and the methods of researching the same process; also, trainee teachers would have hands-on practice opportunities to apply theory in practice.

Absztrakt. A mesealapú idegennyelv-tanítás előnyeit a nyelvpedagógia már régen felismerte és elismerte (l. Ellis & Brewster, 1991). Ennek ellenére a kárpátaljai magyar iskolákban ez a nyelvtanítási eljárás nincs elterjedve. Ezért fontosnak tartottuk, hogy megismertessük angol és ukrán szakos hallgatóinkat ennek az eljárásnak a módszertani alapjaival. Vizsgálódásunk során a részt vevő 25 diák kutatási naplóját elemeztük. Az eredmények azt bizonyítják, hogy a mesealapú tanítás pozitív hatással van a tanulók beszédértésére és szókincsfejlődésére. Kutatásunk pedagógiai implikációjaként pedig hangsúlyozzuk, hogy reményeink szerint a mesealapú nyelvtanítás mint nyelvpedagógiai eljárás bekerül a kötelezően tanítandó témák közé a szaktanárképzésben Az angol nyelv oktatásának módszertana c. tárgyból a II. Rákóczi Ferenc Kárpátaljai Magyar Főiskolán.

Резюме. Метод навчання іноземним мовам за допомогою казок є вже давно відомим і визнаним (див. Ellis & Brewster, 1991). Попри це в угорськомовних школах Закарпаття цей метод не розповсюджений. Мета роботи – представити студентам, майбутнім вчителям англійської та української мов, основи методики навчання іноземним мовам за допомогою казок. У ході дослідження проаналізовано результати, які отримано від 25 студентів – учасників дослідження. Отримані результати засвідчили, що навчання мови за допомогою казок має позитивний вплив на розвиток мовлення та лексичного запасу учнів. З точки зору підготовки майбутніх фахівців, вчителів іноземних мов, у Закарпатському угорському інституті ім. Ференца Ракоці ІІ було б доцільно до дисципліни „Методика навчання англійської мови” включити теми, пов’язані з методом навчання за допомогою казок.
http://www.kmf.uz.ua/hun114/letoltes/acta/acta2011_1.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/137286
Keywords: stories; EYFL; language learning; English classroom